2002
DOI: 10.1254/jjp.88.146
|View full text |Cite
|
Sign up to set email alerts
|

Existence of Functional α1A- and α1D- but No α1B-Adrenoceptor Subtypes in Rat Common Carotid Arteries

Abstract: ABSTRACT-Using the cannula inserting method, vasoconstrictor responses to a1-adrenoceptor agonists (noradrenaline [NA], phenylephrine [PE] and methoxamine [ME]) and effects of a 1-adrenoceptor antagonists (WB4101, chloroethylclonidine [CEC] and BMY7378) were investigated in isolated and perfused rat common carotid arteries. The rank order of agonist potency and efficacy was NA = PE > ME. Either WB4101 or BYM7378 inhibited NA-and PE-induced constrictions in a dose-related manner. CEC did not inhibit the NA-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…α 1D ‐ARs mediate both relaxation and contraction induced by PhE in rat carotid . We confirmed these findings, pointing an important dual opposite effect mediated by α 1D ‐ARs on carotid tone.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…α 1D ‐ARs mediate both relaxation and contraction induced by PhE in rat carotid . We confirmed these findings, pointing an important dual opposite effect mediated by α 1D ‐ARs on carotid tone.…”
Section: Discussionsupporting
confidence: 85%
“…This analysis is reliable because antagonist potency represents an accurate estimative of receptor affinity . BMY7378 is a well‐known reversible competitive antagonist of α 1D ‐ARs, and the appropriated equilibrium time for the antagonist (30 min) was reached during our bioassays. Interestingly, we showed that BMY7378 produced an unsurmountable antagonism on PhE‐induced relaxation despite its classical surmountable antagonism on PhE‐induced contraction.…”
Section: Discussionmentioning
confidence: 99%
“…Their antagonists can relax the arteriole and vein so as to decrease the standing and lying blood pressure. There are functional α 1A -and α 1D -adrenoceptor subtypes in response to the vasoconstriction of the rat common carotid arteries, but no α 1B -adrenoceptor subtype [10] . The analysis of mutant mice has provided some insight into the physiological role of each α 1 -adrenoceptor subtype in the regu- lation of blood pressure.…”
Section: Resultsmentioning
confidence: 93%
“…, 1997; Yan et al. , 2001; Chiba & Tsukada, 2002). The aim of the present study was to characterize the postsynaptic α 1 ‐adrenoceptor subtype(s) mediating vasoconstrictor function in isolated EDVs by the use of selective agonists and antagonists.…”
Section: Introductionmentioning
confidence: 99%
“…The α 1 ‐adrenoceptor subtypes are important mediators of smooth muscle contraction and hypertrophic growth (Piascik & Perez, 2001) and their presence in the vasculature has been reported in a variety of species, including the rat (Chiba & Tsukada, 2002; Arévalo‐León et al. , 2003), rabbit (Satoh et al.…”
Section: Introductionmentioning
confidence: 99%